Green Synthesis of 1H-pyrazolo[1,2-b]phthalazinedione-2-carbonitriles in the Presence of L-proline - Habibi, Davood; Shojaei, Saeedeh; Heydari, Somayyeh (Current Organocatalysis, 2021)
Background: Pyrazolophthalazinedione derivatives show various biological activities such as anti-bacterial, anti-cancer, anti-coagulant, anti-convulsant, anti-fungal, anti-hypoglycemic, anti-inflammatory, anti-tumor, anti-viral, cardiotonic, cytotoxic and vasorelaxant activities. Objective: The purpose of this study was to synthesize compounds that have various medicinal properties. Methods: Diverse 3-amino-5,10-dioxo-1-phenyl-5,10-dihydro-1H-pyrazolo[1,2-b]phthal-azine-2– carbonitriles were synthesized from the one-pot three components green synthesis of phthalhydrazides, aromatic aldehydes and malononitrile in the presence of the proline organocatalyst in ethanol at reflux conditions in excellent yields. Results: Proline was used as an efficient organocatalyst for the one-pot three components green synthesis of diverse pyrazolophthalazinecarbonitriles. In the absence of the proline organocatalyst, the yield was very low. Also, electron withdrawing or electron releasing groups don’t have a meaningful effect on the reaction times and the structures of all products were in agreement with their IR and NMR spectra. Conclusion: In the IR spectra, the appearance of the sharp NH2 and the CN peaks at about 3300 and 2300 cm-1, respectively confirm formation of the products.
Keywords: proline